Evaluating the predictive value of fetal Doppler indices and neonatal outcome in late-onset preeclampsia with severe features: a cross-sectional study in a resource-limited setting - Eman Mohamed Ibraheim Moawad; Amr Samir Fouad Tammam; Maha Mohamed Mosaad; Hadeer Mashaal El Sayed; Adel Atef (BMC, 2022)
Abstract Background Preeclampsia constitutes a major health problem with substantial maternal and perinatal morbidity and mortality. The aim of this study was to detect the diagnostic efficacy of fetal Doppler in predicting adverse outcomes in severe late onset preeclampsia (LOP). Methods A prospective study was conducted among childbearing women who presented with severe LOP and matched controls. Umbilical artery (UA) and middle cerebral artery (MCA) Doppler indices including pulsatility index (PI), resistance index (RI), systolic/diastolic ratio (S/D) and cerebroplacental ratio (CPR) were measured. Results All UA indices were significantly higher in the case group compared to the controls (p < 0.001). UA PI and RI were significantly correlated with all neonatal adverse outcomes except cord pH status (p < 0.05). Abnormal CPR was the most sensitive index that positively correlated with intrauterine growth retardation (IUGR), low 5- minute Apgar score and neonatal intensive care unit admission (79, 72.8 and 73.3%, respectively). In the same context, Abnormal UA PI and RI represented the most specific tool for predicting IUGR, low 1- and 5- minutes Apgar score with positive predictive values were 52, 87 and 57%, respectively. Conclusion In severe LOP, UA Doppler remains the preferential indicator for adverse birth outcomes with CPR is the best index that could be solely used for predicting such outcome.